Clinical Impact of the Histopathological Index and Neuroimaging Features Status in Primary Central Nervous System Diffuse Large B-Cell Lymphoma: A Single-Center Retrospective Analysis of 51 Cases - Qi, Zhou; Duan, Lei; Yuan, Guoqiang; Liu, Jianli; Li, Jian; Li, Guoqiang; Yu, Yue; Xu, Yanlong; Ma, Shangxian; Pan, Yawen; Zhang, Yinian (Frontiers in Oncology, 2022)
Primary central nervous system diffuse large B-cell lymphoma (PCNS-DLBCL) is an uncommon non-Hodgkin lymphoma subtype, and its clinical and pathological characteristics remain unclear. PCNS-DLBCL patient data were retrospectively evaluated to determine clinical and pathological characteristics and prognostic factors. Further, prognoses were calculated by Kaplan-Meier and Cox regression models based on clinical observations. In total, 51 immunocompetent patients were enrolled. The median age was 55 (range, 16-82) years, and the male-to-female ratio was 3:2. Headache (n = 19; 37 %) and the frontal lobe (n = 16; 31 %) were the most common presenting symptom and location, respectively. The median follow-up was 33 (range, 3-86) months, the median overall survival (OS) and progression-free survival (PFS) were 18 months (95 % confidence interval [CI], 21.2-34.2) and 15 months (95 % CI, 16.9-28.7), respectively. Ki-67, cluster of differentiation-3, deep brain involvement were independent prognostic markers. Moreover, multifocal lesions and deep brain involvement were unfavorable independent prognostic markers for PFS. This study indicates that targeted drug development for adverse prognostic factors is possible and provides guidance for clinical treatment decision-making.